2014
DOI: 10.1165/rcmb.2013-0142oc
|View full text |Cite
|
Sign up to set email alerts
|

Proteinase-Activated Receptor-1, CCL2, and CCL7 Regulate Acute Neutrophilic Lung Inflammation

Abstract: PAR1 plays a central role in mediating the interplay between coagulation and inflammation, but its role in regulating acute neutrophilic inflammation is unknown. We report that antagonism of PAR1 was highly effective at reducing acute neutrophil accumulation in a mouse model of LPS-induced lung inflammation. PAR1 antagonism also reduced alveolar-capillary barrier disruption in these mice. This protection was associated with a reduction in the expression of the chemokines, CCL2 and CCL7, but not the proinflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 50 publications
4
75
0
Order By: Relevance
“…It has previously been shown that CCL7 also binds to CCR3 on eosinophils to induce chemotaxis and activation (19). Airway epithelial cells and macrophages produce CCL7, which may orchestrate cell recruitment in the context of oxidative stress (20,21). Induction of CCL7 during viral infections has been observed in asthmatic patients (22) and in models of RV infection dissecting the role of CCL2 (23).…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that CCL7 also binds to CCR3 on eosinophils to induce chemotaxis and activation (19). Airway epithelial cells and macrophages produce CCL7, which may orchestrate cell recruitment in the context of oxidative stress (20,21). Induction of CCL7 during viral infections has been observed in asthmatic patients (22) and in models of RV infection dissecting the role of CCL2 (23).…”
Section: Discussionmentioning
confidence: 99%
“…34,38 Additionally, MCP-1 has been shown to act as a neutrophil chemoattractant in a number of acute and chronic inflammatory models, with recent data suggesting that MCP-1 may have a significant and key role to play in neutrophil recruitment and infiltration in the lung. [38][39][40][41] It has also been proposed to indirectly regulate KC and MIP-2 expression during pulmonary Escherichia coli infection. 38 Furthermore, MCP-1 has been shown to play an important role in the bacterial clearance, and a deficiency of MCP-1 resulted in attenuation of immune cell influx as neutrophil and macrophages were reduced in MCP-1 −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we have demonstrated that neutralizing CCL2, or the related chemokine CCL7, significantly diminishes neutrophil accumulation in the air spaces of LPS-challenged mice (123). Furthermore, neutrophils isolated from inflamed lungs displayed decreased expression of cell surface CXCR2 and increased expression of CCR1 and CCR2 (but not CCR3).…”
Section: Other Chemokines Involved In Neutrophil Migrationmentioning
confidence: 92%
“…It is therefore becoming increasingly clear that the neutrophilic chemokine network within the lung is more complex than previously thought and may be dependent on the contextual influence of several inflammatory and chemotactic factors. It is also likely that the migration of neutrophils into various tissue microcompartments, for example endothelial vs. epithelial, is regulated by distinct sets of chemotactic cues differentially expressed within certain lung microenvironments (123), suggesting there may exist a significant amount of nonredundancy within the lung chemokine network (Tables 1 and 2). The functional capacity of individual chemokines may need to be considered within the context of the surrounding inflammatory milieu and the tissue compartment in which they operate.…”
Section: Other Chemokines Involved In Neutrophil Migrationmentioning
confidence: 99%